EFEKTIVITAS PUPUK MAJEMUK DAN Cu TERHADAP PERTUMBUHAN VEGETATIF TANAMAN KELAPA SAWIT (Elaeis guineensis Jacq.) DI LAHAN GAMBUT - Siallagan, Eko Jaya; ', Wardati (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This studyaims to determine the effective eness of compound fertilizer and Cuon the vegetative growth of oil palm (Elaeisguineensis Jacq.) inpeat land.This research has been carried out in village Rantau Bais ,sub-district Tanah Putih, Rokan Hilir regency from March to July 2014. This study used arandomized block design (RBD) factorial consisting of two factors. First factoris thedoses of compound fertilizer NPK (M),consists of 4 levels is: without NPK fertilizer, 400g/plant NPKfertilizer application, 600g/plant NPK fertilizer as and 800g/plant NPK fertilizer. Second factoris thedoses of Cu(C)fertilizerin4levels is: withoutCu fertilizer application, 25g/plant Cufertilizer application, 50g/plant fertilizer application and 75g/plant Cufertilizer aplication. Parameter observed was the increase in plant height, number of fronds, added girth and length fronds. Data were analyzed statistically using ANOVA followed by Duncan’s test at the 5% level. The results showed that the best interaction demonstrated by NPK compound fertilizers of 800 g/plant and fertilizer Cu of 75 g/plant was effective in increasing the length of the stem but not effective in increasing plant height, number of fronds and increase girth. The NPK compound fertilizers are not effectivelyall parameters. Copper fertilizer of 75 g/plant was effective in increasing the length of the stem, but not effectively for other parameters. Keywords : Cu, peat, oil palm, compound fertilizer.